Errors in English Descriptive Text Produced by High School Students in Manado - Meily Ivane Esther Neman; Virginia Sabatini Kamuh (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Studying errors in English as a foreign language is crucial for both teachers and learners. This study aims to identify and analyze the types of errors in writing descriptive texts produced by students at SMA N 8 Manado, with a focus on determining the most prevalent types. This qualitative study employs the classification error theory based on Dulay et al. (1982), namely, the surface strategy taxonomy, omission, misordering, addition, and misformation. The students in SMA N 8 Manado, as the sample of this study, were asked to write a paragraph about their goals. The results of this study showed the percentage of errors made by students in writing descriptive text, which are, omission error (25,23%), error of misordering (7,47%), error of addition (10,28%), and error of misformation (57,94). This study also found other errors that are produced by some students that are not included in the classification of errors by Dulay et al (1982), they are errors in punctuation and capitalization.